ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KETEPATAN WAKTU PELAPORAN KEUANGAN PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Auliyah, Iriana (Universitas Muhammadiyah Parepare, 2020)
This study aims to determine the effect of profitability, ownership structure, leverage, company size and company size on the timeliness of financial reporting. The data used in this study are secondary data, namely data on return of assets, ownership structure, debt to equity ratio, company size, and company age with a period of 5 years (2015-2019), the data were analyzed and processed by multiple linear regression method. The results of this study indicate that profitability has a positive and significant effect on timeliness of financial reporting; ownership structure has a positive but not significant effect on timeliness of financial reporting; leverage has a positive but not significant effect on timeliness of financial reporting; company size has a positive but not significant effect on timeliness of financial reporting; company age has a positive and significant effect on timeliness of financial reporting; profitability, ownership structure, leverage, company size, and company age together affect on the timeliness of financial reporting.